Penatalaksanaan Enterobiosis pada Anak Melalui Pendekatan Kedokteran Keluarga - Rani Salsabila Efendi; Syahrizal, Syahrizal; Berliana Dara Safitri (Yayasan Literasi Sains Indonesia, 2024)
Enterobiosis in children remains a serious public health problem in many developing countries, including Indonesia. The epidemiology of Enterobiasis disease shows a high prevalence especially in areas with poor sanitation and limited access to health services. The pathophysiology of Enterobiasis disease involves infection with parasitic worms such as Enterobius vermicularis which can cause various health complications in children, including anemia, impaired growth, and impaired cognitive development. Service activities carried out by providing advice/support to Enterobiosis patients are considered through self-history, home visits by adopting a holistic and comprehensive family medicine approach. The aim of patient counseling/support is to increase awareness of the disease and improve the quality of life of the patient. The results of service activities and home visits show that patients have a better understanding of their disease and the level of compliance with treatment and healthy living behavior, which affects the success of treatment. Comprehensive treatment with a family medicine approach is needed to identify problems in various ways, support the success of therapy, and improve the quality of life of patients.